Effect of perforation size and substrate bag fruiting position on the morphology of fruiting bodies and clusters in Pleurotus ostreatus (Jacq.) P. Kumm - Bandyra, Iryna; Бандура, Ірина Іванівна; Бандура, Ирина Ивановна; Isikhuemhen, S.; Kulyk, Alina; Кулик, Аліна Степанівна; Кулик, Алина Степановна; Serdyuk, Maryna; Сердюк, Марина Єгорівна; Сердюк, Марина Егоровна; Sukharenko, Olena; Сухаренко, Олена Іванівна; et al. (My University, 2021)
EN : Perforation or fruiting hole size on substrate bags control cluster sizes and morphology in exotic mushroom cultivation. The effect of three different perforation sizes on substrate bags (factor A: 50, 100, and 150 mm) and their positioning on the shelves (factor B: Horizontal, vertical, and slant) on the crop and various morphological characteristics in Pleurotus ostreatus was studied. Microclimatic conditions for fruiting were 16±1°C, 87±3% RH; 230±42 lux illumination. The formula for calculating area of ellipse was modified and used for the area of mushroom cap. Results indicated that the total fruit body yield and biological efficiency (BE) in the bags set in horizontal position were 10% lower than other treatments. The effect of perforation size on mushroom cluster sizes was more on the substrate blocks in the horizontal position. There was a linear correlation between perforation size and fruiting body cluster sizes. Results suggest that the 50 mm perforation on bags in vertical and slant positions gave fruiting body clusters sizes 186–196 mm width and 122–154 mm height, with 92.36±6.48% BE. The cluster size indicated is the best fit for standard packaging containers used in commercial oyster mushroom production in Ukraine.
Keywords: biological efficiency; fruiting body morphology; fruiting position; mushroom clusters size; pleurotus ostreatus; weight loss coefficient